EFFORTS TO ERADICATE AND OVERCOME DRUGS BY THE POLICE - Wilhelmus Renyaan (HERMENEUTIKA : Jurnal Ilmu Hukum, 2023)
This writing aims to find out the Efforts to Eradicate and Control Drug Crime and the obstacles by the Police. The type of research used by researchers in writing this thesis is the Sosio Juridical research type, which means science that analytically and empirically analyzes or studies the interrelationships between law and social phenomena related to the research object being studied. The results of the research show that it is necessary to reconstruct efforts to overcome and eradicate drugs. In an effort to tackle and eradicate narcotics crime, priority should be given to non-penal policies because non-penal policies basically lead to preventive efforts. Education about the dangers of narcotics abuse should be included in the education curriculum at the elementary, secondary and tertiary education levels.